PoLAR-FIT: Pliocene Landscapes and Arctic Remains—Frozen in Time - Gosse, J.C.; Ballantyne, A.P.; Barker, J.D.; Csank, A.Z.; Fletcher, T.L.; Grant, G.W.; Greenwood, D.R.; MacPhee, R.D.E.; Rybczynski, N. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
This short summary presents selected results of an ongoing investigation into the feedbacks that contribute to amplified Arctic warming. The consequences of warming for Arctic biodiversity and landscape response to global warmth are currently being interpreted. Arctic North American records of largescale landscape and paleoenvironmental change during the Pliocene are exquisitely preserved and locked in permafrost, providing an opportunity for paleoenvironmental and faunal reconstruction with unprecedented quality and resolution. During a period of mean global temperatures only ~2.5°C above modern, the Pliocene molecular, isotopic, tree-ring, paleofaunal, and paleofloral records indicate that the High Arctic mean annual temperature was 11–19°C above modern values, pointing to a much shallower latitudinal temperature gradient than exists today. It appears that the intense Neogene warming caused thawing and weathering to liberate sediment and create a continuous and thick (>2.5 km in places) clastic wedge, from at least Banks Island to Meighen Island, to form a coastal plain that provided a highway for camels and other mammals to migrate and evolve in the High Arctic. In this summary, we highlight the opportunities that exist for research on these and related topics with the PoLAR-FIT community.